δ13C decreases in the upper western South Atlantic during Heinrich Stadials 3 and 2 - Campos, Marília C. (2017)
Abrupt millennial-scale climate change events of the last deglaciation (i.e. Heinrich Stadial 1 and the Younger Dryas) were accompanied by marked increases in atmospheric CO2 (CO2atm) and decreases in its stable carbon isotopic ratios (δ13C), i.e. δ13CO2atm, presumably due to outgassing from the ocean. However, information on the preceding Heinrich Stadials during the last glacial period is scarce. Here we present δ13C records from two species of planktonic foraminifera from the western South Atlantic that reveal major decreases (up to 1%) during Heinrich Stadials 3 and 2. These δ13C decreases are most likely related to millennial-scale periods of weakening of the Atlantic meridional overturning circulation and the consequent increase (decrease) in CO2atm (δ13CO2atm). We hypothesise two mechanisms that could account for the decreases observed in our records, namely strengthening of Southern Ocean deep-water ventilation and weakening of the biological pump. Additionally, we suggest that air-sea gas exchange could have contributed to the observed δ13C decreases. Together with other lines of evidence, our data are consistent with the hypothesis that the CO2 added to the atmosphere during abrupt millennial-scale climate change events of the last glacial period also originated in the ocean and reached the atmosphere by outgassing. The temporal evolution of δ13C during Heinrich Stadials 3 and 2 in our records is characterized by two relative minima separated by a relative maximum. This "w structure" is also found in North Atlantic and South American records, further suggesting that such a structure is a pervasive feature of Heinrich Stadial 2 and, possibly, also Heinrich Stadial 3.